Goals for Adolescent Participation in Organized Youth Programs: Views From Adolescent-Parent Dyads. Issue 2 (March 2023) - Munoz, Lorraine; Raffaelli, Marcela; Kang, Hyeyoung
This study investigated the goals adolescents and parents have for the adolescent's participation in an organized youth program. Open-ended interviews were conducted with 52 adolescents from 13 project-based youth programs and one of their caregivers. Adolescents (aged 13–18; 56% female) were ethnically diverse (46% Latinx, 29% European American, 19% African American, and 6% other). Caregivers ( M age 43.15 years) were predominantly female (80%) and biological or adoptive parents (94%); about half had been born in the United States. Qualitative and quantitative analyses were conducted to examine goal content and congruence between adolescents and parents. Interview data were inductively coded following a consensus team approach. Thirteen goal categories were identified: nine were described by both adolescents and parents (e.g., skill-building and socialization) and two were unique to adolescents and two to parents. More than half (56%) of adolescent-parent dyads reported at least one matching goal. In general, adolescents tended to emphasize short-term objectives and parents long-term outcomes. Collectively, findings indicate that adolescents and their parents view organized programs as salient contexts to pursue youth's personal goals. Findings have implications for theory, research, and practice.